2018
DOI: 10.1089/jpm.2018.0152
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of End-of-Life Care for Patients with Hematologic Malignancies and the Role of Race/Ethnicity

Abstract: Our findings suggest that racial/ethnic minority patients with HM have higher utilization of care at the end-of-life and lower rates of advance directives compared with NHW patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…The finding of more aggressive end-of-life care among decedents of Chinese or South Asian ethnicity is similar to the findings of other large-scale quantitative analyses assessing end-of-life care for people from ethnic minorities in North America such as Hispanic or black people. 16,44,45 Although each ethnic group has multiple unique underlying contributors to these findings, some factors such as provider-patient ethnicity discordance, decreased socioeconomic resources and discrimination may be common to different minority ethnicities. 5,46,47 We found contrasting results with respect to receipt of palliative care in the final 6 months of life, with decedents of South Asian ethnicity less likely, and decedents of Chinese ethnicity more likely, to receive palliative care relative to decedents from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of more aggressive end-of-life care among decedents of Chinese or South Asian ethnicity is similar to the findings of other large-scale quantitative analyses assessing end-of-life care for people from ethnic minorities in North America such as Hispanic or black people. 16,44,45 Although each ethnic group has multiple unique underlying contributors to these findings, some factors such as provider-patient ethnicity discordance, decreased socioeconomic resources and discrimination may be common to different minority ethnicities. 5,46,47 We found contrasting results with respect to receipt of palliative care in the final 6 months of life, with decedents of South Asian ethnicity less likely, and decedents of Chinese ethnicity more likely, to receive palliative care relative to decedents from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…7 Retrospective cohort study (2010)(2011)(2012)(2013)(2014)(2015) of hospital utilization among racial/ethnic minority patients with hematologic and non-hematologic malignancies suggested that racial/ethnic minority patients with hematologic malignancies have higher utilization of care at the end of life and lower rates of advance directives compared with non-Hispanic patients. 49 Delay of initiation of outpatient palliative care consultation among non-Hispanic Black cancer patients also highlights a racial disparity. 53 Ahluwalia and colleagues (2018) examined 139 systematic reviews published after 2013, when the third edition of National Consensus Project Clinical Practice Guidelines for Quality Palliative Care was published.…”
Section: Methodsmentioning
confidence: 99%
“…175 Existing data clearly show that the odds of delayed hospice referral near the end of life were greater in non-Hispanic Blacks than in non-Hispanic Whites. 49 The disparity in hospice use among ethnic minority populations is a complex and nuanced problem, involving numerous interrelated barriers. 41 A systematic review of both qualitative and quantitative research identified factors that contribute to the underuse of hospice services by non-Hispanic Blacks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some debate about whether the use of chemotherapy near death represents a reliable marker of aggressiveness of care in this population, given the fact that anticancer treatment may be appropriate for some patients with HM. 14,15 Indeed, hematologic specialists reported to feel more comfortable to prescribe systemic therapy to patients with poor performance status in the last month of life than solid tumor specialists. 16 In the acute care setting, clinical complications and relapses in HM are usually better investigated with medical imaging, which helps explain why the majority of patients in this study had undergone CT scans and MRI examinations prior to death.…”
Section: Discussionmentioning
confidence: 99%